PENINGKATAN KUALITAS TIM KERJA (WORK TEAMS) PADA KINERJA MANUFAKTUR - Widiastuti, Imron (SISTEM Jurnal Ilmu Ilmu Teknik, 2015)
One of the central components of the participative management approach is getting employee to collaborative and works together on various organizational projects. A basic aspect of modern organizational life is that there are fewer work assignments that are fully performed by one individual alone. More usually, teamwork groups composed of two or more persons who shall coordinate with each other in order to accomplish the manufacturing project to fulfill various organizational needs.    This paper attempts to explain the quality aspect in term of effective team performance. Quality had emerged as philosophy in continuing improvement at all various organizational levels. Quality and labor productivity should be improved upon formation of the teams.